Interação de genótipos de milho vs locais, anos e épocas de semeadura - Buzinaro, Rodolfo [UNESP] (2014)
This work aims to evaluate the G x E interaction and its unfolding in simple and complex part, in order to study the best locations and sowing dates for evaluation of genotypes grain yield of maize, at Jaboticabal-SP and Campo Alegre de Goiás-GO. Four experiments were carried out in randomized blocks design with three replications and 17 genotypes where 13 are experimental synthetic, three varieties and a commercial hybrid. Two seasons of cultivation were evaluated for each location. Environmental stratification was measured by the traditional method of Lin (1982) and the dissimilarity has been estimated by the method of Cruz & Castoldi (1991), in addition to the Pearson correlation coefficient between environments pairs. The results showed that there was disagreement between the methods used. Breeding programs must prioritize evaluations in years and locations to the detriment of different sowing dates in order to discriminate the best genotypes and make precise recommendations